Digital geoarchaeology: new techniques for interdisciplinary human-environmental research - Siart, Christoph; Forbriger, Markus; Bubenzer, Olaf (Springer, 2018)
Modern archaeology can be considered as an interdisciplinary approach that increasingly combines different methods and datasets to answer questions about ancient cultures and their remains. Having its major focus on new technologies and multi-method research approaches, the book promotes interdisciplinary studies between different disciplines such as archaeology, computer sciences, geography, geoinformatics, geodesy, history, etc. Common fields of work as well as future challenges are identified and discussed from different scientific perspectives. Each chapter starts with a general introduction to the topic followed by case studies. By stimulating knowledge transfer and collaboration, Digital Geoarchaeology contributes to an effective protection of cultural heritage and a better understanding of ancient landscapes along with their forming processes. This book includes topics and applications such as geographic and archaeological information systems, remote sensing, e.g. satellite imagery, aerial photographs, terrestrial and airborne laser scanning, digital image processing and pattern recognition, digital elevation models, 3D and 4D visualization and landscape reconstruction, geophysical prospecting, e.g. ERT, SRT, GPR as well as spatiotemporal analysis
Keywords: Geoinformationssystem; Fernerkundung; Geoarchäologie